Stability of maternal mRNA in Xenopus embryos: role of transcription and translation. - Duval, C (1990)
The first 12 cell divisions of Xenopus laevis embryos do not require gene transcription. This means that the regulation of gene expression during this period is controlled at post transcriptional levels and makes Xenopus early development a potentially interesting biological system with which to study the mechanisms involved. We describe here the stability characteristics of several maternal Xenopus mRNAs which are deadenylated soon after fertilisation (J. Paris and M. Philippe, Dev. Biol., in press). We show that these mRNAs were only degraded in the embryo after the midblastula transition (MBT), when gene transcription was initiated. The kinetics with which the deadenylated maternal mRNAs decreased in the post-MBT embryos showed sequence specificity. The degradation of these mRNAs after the MBT was inhibited by cycloheximide but was not affected by dactinomycin. Therefore, the destabilization of these mRNAs does not appear to be initiated by new embryonic gene transcripts. Sequence comparisons of the 3' untranslated region of these mRNAs identified several motifs which may be involved in the posttranscriptional control of these gene products.